2013
DOI: 10.1128/aem.01854-13
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Strain Engineered for Treatment of Soil-Transmitted Helminth Diseases

Abstract: c Soil-transmitted helminths (hookworms, whipworms, and large roundworms) are agents of intestinal roundworm diseases of poverty that infect upwards of 2 billion people worldwide. A great challenge in treating these diseases is the development of anthelmintic therapeutics that are inexpensive, can be produced in great quantity, and are capable of delivery under varied and adverse environmental conditions. A potential solution to this challenge is the use of live bacteria that are acceptable for human consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 52 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…We therefore set out to deliver Cry5B, without purification of the protein, as part of a dead bacterial product (or "paraprobiotic" (50)). To make a Cry5B paraprobiotic, we initially turned to and produced Cry5B spore-crystal lysates, which have been used for most published in vivo studies of Cry5B anthelmintic efficacy as well as all Bt insecticidal production and use (31,33,34,43,45). We attempted to inactivate (kill) the spores without losing activity of the crystal protein using gamma irradiation (51).…”
Section: Inactivated Bacterium With Cytosolic Crystal (Ibacc)mentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore set out to deliver Cry5B, without purification of the protein, as part of a dead bacterial product (or "paraprobiotic" (50)). To make a Cry5B paraprobiotic, we initially turned to and produced Cry5B spore-crystal lysates, which have been used for most published in vivo studies of Cry5B anthelmintic efficacy as well as all Bt insecticidal production and use (31,33,34,43,45). We attempted to inactivate (kill) the spores without losing activity of the crystal protein using gamma irradiation (51).…”
Section: Inactivated Bacterium With Cytosolic Crystal (Ibacc)mentioning
confidence: 99%
“…Hamsters were infected with A. ceylanicum, and the infestations were allowed to proceed to mature adults with the appearance of parasite eggs (fecundity) excreted into the hamster feces (31,33,44). These hamsters were then treated with IBaCC produced in our laboratory containing 10 mg/kg Cry5B ( Figure 5A) or treated with IBa (vector-only control produced at the same time and processed identically to Cry5B…”
Section: Cry5b Ibacc Is a Potent Anthelmintic In Vivo Against Both Gementioning
confidence: 99%
See 1 more Smart Citation
“…ZB183 is a viable genetically modified B. subtilis strain that constitutively expresses an acetaldehyde dehydrogenase enzyme, AcoD, from C. necator (which has been known by a number of other names, including Alcaligenes eutrophus, Ralstonia eutropha, and Hydrogenomonas eutropha). The parental strain is B. subtilis PY79, a widely used strain in laboratory studies with a published sequence, that is lacking of many mobile genetic elements found in other B. subtilis strains, and has been found to be nontoxic to vertebrates and has been studied in humans [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, B. subtilis PY79 was used to express the Bacillus thuringiensis anthelmintic protein Cry5B to control soil-transmitted helminth diseases (19). B. subtilis strain 168 has been well characterized.…”
mentioning
confidence: 99%